Why Do Some Denizens Reject Naturalisation? The Case of Long-term Immigrants in Poland - Andrejuk, Katarzyna (SocietàMutamentoPolitica, 2016)
The article analyses reasons and context of the decision not to naturalise, made by long-term immigrants in Poland. The text encompasses description of the legal context of naturalisation in Poland, statistical data about long-term residents from various diasporas and number of citizenship acquisitions. The article focuses on four case studies of migrants from the United Kingdom, Lithuania, Vietnam and India in order to examine and interpret the declared reasons of the lack of naturalisation. In general, three types of reasons are distinguished: psychological (lack of sufficient sense of belonging), bureaucratic (costs, length and complicated character of the procedure) and legal-political (prohibition of dual citizenship in the country of origin, possession of a status of a permanent resident).